Preparation method and device of nano-structure magnesium alloy block material

By repeatedly passing incompletely dense semi-solid magnesium alloy blocks through the titanium mesh under the action of electrical pulses and pressure, the problem of difficulty in preparing nanomagnesium alloy block materials in the prior art is solved, and the nano-scale microstructure construction and complete densification of the material are realized, and the material performance and preparation efficiency are improved.

CN119506647AActive Publication Date: 2025-02-25AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411358747.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-25
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

It is difficult to effectively prepare magnesium alloy bulk materials with nanoscale microstructures, and during the violent plastic deformation process, changes in the material appearance affect the deformation effect.

Method used

The incompletely dense semi-solid magnesium alloy block is repeatedly passed through the titanium mesh under the action of electrical pulses and pressure, and its internal microstructure is cut to achieve nano-narrowization, and finally achieve complete densification at a certain temperature and pressure.

Benefits of technology

The construction of magnesium alloy bulk materials from semi-solid to solid state, from micron to nanoscale microstructures is realized, which improves the strength and toughness of the material, and does not require excessive tonnage equipment during the preparation process, and is highly efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506647A_ABST
    Figure CN119506647A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and device of a nano-structure magnesium alloy block material, and adopts the technical scheme that an incompletely-compact semi-solid magnesium alloy block material repeatedly passes through a titanium mesh under the action of electric pulse and pressure, and the internal microstructure of the incompletely-compact semi-solid magnesium alloy block material is repeatedly cut, so that the nano-structure magnesium alloy block material is prepared. And finally, the magnesium alloy block material is completely densified at a certain temperature and pressure. The method has the advantages that 1, through the scheme of the invention, the construction of a magnesium alloy block material from a semi-solid state to a solid state and from a micron level to a nano level microstructure is realized; 2, in the scheme of the invention, for the preparation of a magnesium alloy block material, equipment with overlarge tonnage is not needed, and severe plastic deformation is realized; and 3, in the implementation process of the scheme, the magnesium alloy block material is always kept at medium and low temperature, grain growth is avoided, and the preparation efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention discloses a method and a device for preparing a nanostructured magnesium alloy block material, belonging to the technical field of magnesium alloy component manufacturing. Background Art

[0002] Grain refinement is the main method known to improve both strength and toughness. There are two main methods for preparing nanocrystals: Top-down process, which aims to refine the grains of conventional tissue materials; Bottom-up process, which aims to synthesize fine grain structures on the basis of atoms and molecules. Common preparation methods include: rapid solidification, vapor deposition, mechanical alloying, low-temperature metal forming and severe plastic deformation, among which severe plastic deformation is considered to be the most suitable for industrial production. Compared with traditional plastic deformation processes, the design purpose of severe plastic deformation technology is to keep the shape of the blank basically unchanged during the deformation process, so that the strain can be achieved without being affected by the shape of the material. Most severe plastic deformation processes are actually a cyclic deformation process, but there are usually changes in the deformation path. Summary of the invention

[0003] The present invention is designed to address the above-mentioned existing technical situation and provides a method and device for preparing a nanostructured magnesium alloy bulk material. Its purpose is to prepare a magnesium alloy bulk material with a nanoscale microstructure through an incompletely dense semi-solid magnesium alloy block 7 with the help of electric pulses, titanium mesh, temperature and pressure.

[0004] To achieve the above purpose, the technical solution of the present invention is as follows:

[0005] The technical solution of the present invention proposes a method for preparing a nanostructured magnesium alloy block material. The method is to repeatedly pass an incompletely dense semi-solid magnesium alloy block 7 through a titanium mesh 4 under the action of electric pulses and pressure so that its internal microstructure is repeatedly cut to achieve nano-sizing, and finally the magnesium alloy block 7 is completely densified.

[0006] In practice, the titanium mesh 4 is a mesh structure with rigidity constructed by weaving titanium powder particles on a substrate formed by iron powder particles, with a thickness of 0.1 to 0.5 mm and a pore size of 100 to 1000 nm.

[0007] During implementation, the preparation process of the titanium mesh 4 is: prepare a titanium sheet by 3D printing, the thickness of the titanium sheet is 0.1-0.3 mm, and then use a laser to impact regularly arranged holes on the titanium sheet, the hole diameter is 0.01-0.05 mm, and the holes are spaced 0.01-0.03 mm in the X and Y directions. Repeat the above operation, and stack the titanium sheets together until the thickness reaches 1-3 mm, and the hole depth is consistent with the thickness of the stacked titanium sheets.

[0008] In practice, the density of the incompletely dense semi-solid magnesium alloy block 7 is 85-90%.

[0009] During implementation, when the incompletely dense semi-solid magnesium alloy block 7 passes through the titanium mesh 4, the incompletely dense semi-solid magnesium alloy block 7 is heated to 500-700°C, and the titanium mesh 4 is heated to 200-500°C.

[0010] In order to realize the method described in the present invention, the technical solution of the present invention also proposes a device for preparing a nanostructured magnesium alloy bulk material, which includes an extrusion cylinder 1, a titanium mesh 4 is placed in the middle of the extrusion cylinder 1, and the extrusion cylinder 1 is divided into two left and right spaces. The titanium mesh 4 can rotate 10 to 90 degrees along the central axis. A left pressure head 6 and a left pulse current generator 5 connected to the outside of the titanium mesh 4 are arranged in the left space of the titanium mesh 4, and a right pressure head 3 and a right pulse current generator 2 connected to the outside of the titanium mesh 4 are arranged in the right space of the titanium mesh 4. Both the left pressure head 6 and the right pressure head 3 can move toward the titanium mesh 4 under pressure.

[0011] In practice, the steps of using the device to prepare a nanostructured magnesium alloy bulk material are as follows:

[0012] Step 1: hot isostatic pressing the pure -300--500 mesh magnesium alloy powder at 300-700° C. During the hot isostatic pressing process, the magnesium alloy powder is not completely densified by pressure control to obtain a semi-solid magnesium alloy block 7 with a density of 85-90%, and the material microstructure of the semi-solid magnesium alloy block 7 has a micrometer scale;

[0013] Step 2: Start the left pulse current generator 5 and the right pulse current generator 2 to preheat the titanium mesh 4 and keep it at 200-500° C.;

[0014] Step 3: preheat the semi-solid magnesium alloy block 7 which is not fully dense, and the preheating temperature is 600-750°C. After the preheating is completed, the semi-solid magnesium alloy block 7 is placed in the left space of the extrusion cylinder 1, and the left pressure head 6 is driven to move rightward with pressure, and the moving speed is 1-3 mm / s, until the semi-solid magnesium alloy block 7 passes through the titanium mesh 4. At this time, the semi-solid magnesium alloy block 7 enters the right space of the extrusion cylinder 1, and the titanium mesh 4 is rotated to the next angle, and then the right pressure head 3 is driven to move leftward with pressure, and the moving speed is 1-3 mm / s, until the semi-solid magnesium alloy block 7 passes through the titanium mesh 4. The whole process is completed within 1 minute;

[0015] Step 4: Repeat the process of step 3 for more than five times, then take out the gradually consumed titanium mesh 4, and use the left pressing head 6 and the right pressing head 3 to simultaneously perform bidirectional pressing on the semi-solid magnesium alloy block 7 in opposite directions to obtain a fully dense magnesium alloy block.

[0016] In addition, in the step 4, the pressing temperature of the left pressing head 6 and the right pressing head 3 is 400-500°C.

[0017] The technical solution of the present invention is a method for preparing nano magnesium alloy bulk material between the existing top-down process and bottom-up process, and its design idea has not been reported at home and abroad. The technical solution of the present invention is to use an incompletely dense semi-solid magnesium alloy bulk material, and under the action of electric pulses and pressure, the incompletely dense semi-solid magnesium alloy bulk material repeatedly passes through a titanium mesh, and its internal microstructure is repeatedly cut to achieve nano-crystallization, and finally at a certain temperature and pressure, the magnesium alloy bulk material is completely dense.

[0018] The beneficial effects of the technical solution of the present invention are mainly reflected in:

[0019] 1. Through the scheme of the present invention, the construction of magnesium alloy bulk material from semi-solid to solid, from micron-scale to nano-scale microstructure is realized, and the nano-scale microstructure has dispersion;

[0020] 2. In the scheme of the present invention, for the preparation of magnesium alloy block materials, no equipment with excessive tonnage is required to achieve severe plastic deformation. During the severe plastic deformation process, the titanium mesh plays a role in refining the microstructure. While cutting the magnesium alloy block material that is not fully dense, there are two refining mechanisms. One is mechanical crushing. There are residual magnesium alloy powder particles in the magnesium alloy block material that is not fully dense. When passing through the titanium mesh, the residual magnesium alloy powder particles are cut to achieve nano-crystallization. The other is recrystallization. When the grains pass through the titanium mesh, the grain boundaries are reconstructed. Under the action of the pulse current, the grain boundaries that are forcibly cut are small-angle grain boundaries. After passing through the titanium mesh, recrystallization occurs rapidly, and no growth occurs at low temperature and in a short time.

[0021] 3. During the implementation of the scheme of the present invention, the magnesium alloy block material always maintains a medium-low temperature, thereby avoiding grain growth and improving the preparation efficiency;

[0022] 4. In the solution of the present invention, the titanium mesh is not a whole in the thickness direction, but several layers are stacked together. Such a design can greatly reduce the impact of the magnesium alloy block material on the titanium mesh when passing through the titanium mesh, indirectly improving the rigidity of the titanium mesh and avoiding its premature aging. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a structural schematic diagram of the device described in the technical solution of the present invention DETAILED DESCRIPTION

[0024] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments:

[0025] See attached Figure 1 As shown, the device for preparing the nanostructured magnesium alloy bulk material of the present invention comprises an extrusion cylinder 1, in the middle of which is placed a titanium mesh 4, dividing the extrusion cylinder 1 into two left and right spaces, the titanium mesh 4 being capable of rotating 10 to 90 degrees along the central axis, a left pressure head 6 and a left pulse current generator 5 connected to the outer side thereof being arranged in the left space of the titanium mesh 4, a right pressure head 3 and a right pulse current generator 2 connected to the outer side thereof being arranged in the right space of the titanium mesh 4, and both the left pressure head 6 and the right pressure head 3 being capable of moving toward the titanium mesh 4 under pressure.

[0026] The steps of using the device to prepare nanostructured magnesium alloy bulk material are as follows:

[0027] Step 1: hot isostatic pressing the pure -300--500 mesh magnesium alloy powder at 300-700° C. During the hot isostatic pressing process, the magnesium alloy powder is not completely densified by pressure control to obtain a semi-solid magnesium alloy block 7 with a density of 85-90%, and the material microstructure of the semi-solid magnesium alloy block 7 has a micrometer scale;

[0028] Step 2: Start the left pulse current generator 5 and the right pulse current generator 2 to preheat the titanium mesh 4 and keep it at 200-500° C.;

[0029] Step 3: preheat the semi-solid magnesium alloy block 7 which is not fully dense, and the preheating temperature is 600-750°C. After the preheating is completed, the semi-solid magnesium alloy block 7 is placed in the left space of the extrusion cylinder 1, and the left pressure head 6 is driven to move rightward with pressure, and the moving speed is 1-3 mm / s, until the semi-solid magnesium alloy block 7 passes through the titanium mesh 4. At this time, the semi-solid magnesium alloy block 7 enters the right space of the extrusion cylinder 1, and the titanium mesh 4 is rotated to the next angle, and then the right pressure head 3 is driven to move leftward with pressure, and the moving speed is 1-3 mm / s, until the semi-solid magnesium alloy block 7 passes through the titanium mesh 4. The whole process is completed within 1 minute;

[0030] Step 4. Repeat the process of step 3 for more than five times, then take out the gradually consumed titanium mesh 4, and use the left press head 6 and the right press head 3 to simultaneously perform bidirectional pressing on the semi-solid magnesium alloy block 7 in opposite directions. The pressing temperature of the left press head 6 and the right press head 3 is 400-500°C to obtain a fully dense magnesium alloy block.

Claims

1. A method for preparing a nanostructured magnesium alloy bulk material, characterized by: The method comprises the following steps: repeatedly passing an incompletely dense semi-solid magnesium alloy block (7) through a titanium mesh (4) under the action of pulse current and pressure, so that its internal microstructure is repeatedly cut to achieve nano-crystallization, and finally the magnesium alloy block (7) is completely densified.

2. The method for preparing a nanostructured magnesium alloy bulk material according to claim 1, characterized in that: The titanium mesh (4) is a mesh structure with rigidity constructed by weaving titanium powder particles on a substrate formed by iron powder particles, with a thickness of 0.1 to 0.5 mm and a pore size of 100 to 1000 nm.

3. The method for preparing a nanostructured magnesium alloy bulk material according to claim 1, characterized in that: The preparation process of the titanium mesh (4) is as follows: a titanium sheet is prepared by 3D printing, the thickness of the titanium sheet is 0.1 to 0.15 mm, and then regularly arranged holes are punched out on the titanium sheet by laser, the hole diameter is 0.01 to 0.05 μm, and the holes are spaced 0.01 to 0.03 mm in the X and Y directions. The above operation is repeated, and the titanium sheets are stacked together until the thickness reaches 1 to 3 mm, and the hole depth is consistent with the thickness of the stacked titanium sheets.

4. The method for preparing a nanostructured magnesium alloy bulk material according to claim 1, characterized in that: The density of the incompletely dense semi-solid magnesium alloy block (7) is 80-85%.

5. The method for preparing a nanostructured magnesium alloy bulk material according to claim 1, characterized in that: When the incompletely dense semi-solid magnesium alloy block (7) passes through the titanium mesh (4), the incompletely dense semi-solid magnesium alloy block (7) is heated to 500-700°C, and the titanium mesh (4) is heated to 200-500°C.

6. A device for the method for preparing the nanostructured magnesium alloy bulk material according to claim 1, characterized in that: The device comprises an extrusion cylinder (1), a titanium mesh (4) is placed in the middle of the extrusion cylinder (1), and the extrusion cylinder (1) is divided into two spaces, left and right. The titanium mesh (4) can rotate 10 to 90 degrees along the central axis. A left pressure head (6) and a left pulse current generator (5) connected to the outside of the titanium mesh (4) are arranged in the left space of the titanium mesh (4), and a right pressure head (3) and a right pulse current generator (2) connected to the outside of the titanium mesh (4) are arranged in the right space of the titanium mesh (4). Both the left pressure head (6) and the right pressure head (3) can move toward the titanium mesh (4) under pressure.

7. The device according to claim 6, characterized in that: The steps of using the device to prepare nanostructured magnesium alloy bulk material are as follows: Step 1, hot isostatic pressing pure -300--500 mesh magnesium alloy powder at 300-700° C. During the hot isostatic pressing process, the magnesium alloy powder is not completely densified by controlling the pressure, so as to obtain a semi-solid magnesium alloy block (7) with a density of 85-90%, wherein the material microstructure of the semi-solid magnesium alloy block (7) is at a micrometer scale; Step 2: Start the left pulse current generator (5) and the right pulse current generator (2) to preheat the titanium mesh (4) and keep it at 200-500° C.; Step 3: preheating the semi-solid magnesium alloy block (7) which is not completely dense, with the preheating temperature being 600-750° C. After the preheating is completed, the semi-solid magnesium alloy block (7) is placed in the left space of the extrusion cylinder (1), and the left pressure head (6) is used to drive the semi-solid magnesium alloy block (7) to move rightward under pressure, with a moving speed of 1-3 mm / s, until the semi-solid magnesium alloy block (7) passes through the titanium mesh (4). At this time, the semi-solid magnesium alloy block (7) enters the right space of the extrusion cylinder (1), and the titanium mesh (4) is rotated to the next angle, and then the right pressure head (3) is used to drive the semi-solid magnesium alloy block (7) to move leftward under pressure, with a moving speed of 1-3 mm / s, until the semi-solid magnesium alloy block (7) passes through the titanium mesh (4). The whole process is completed within 1 minute. Step 4: Repeat the process of step 3 for more than five times, then take out the gradually consumed titanium mesh (4), and use the left pressing head (6) and the right pressing head (3) to simultaneously perform bidirectional pressing on the semi-solid magnesium alloy block (7) in opposite directions to obtain a fully dense magnesium alloy block.

8. The device according to claim 7, characterized in that: In the step 4, the pressing temperature of the left pressing head (6) and the right pressing head (3) is 400-500°C.

Citation Information

Patent Citations

  • Method for precipitating large area amorphous, nanocrystalline alloy layer using magnesium alloy surface glow plasma

    CN101008078A

  • Method for manufacturing composite material for carbon nano material and metal material

    CN101070571A

  • Preparation method of fine-grain magnesium alloy doped with nano-particles

    CN103978191A

  • Hot reverse extrusion forming method for titanium alloy cup-shaped part

    CN108838226A